Optimizing Islamic Religious Education Teachers' Competence in Utilizing Technology for Learning in Elementary Schools - Muis, Abd; Chotib, Moch; Muhith, Abd (ATTA`DIB, 2025)
The integration of technology in Islamic Education (PAI) teaching at the elementary school level has become increasingly crucial in the digital era. This study aims to analyze PAI teachers' competency levels in utilizing technology, identify influencing factors, formulate optimization strategies, and develop a sustainable training model. Using a qualitative approach through library research, this study analyzes primary sources from Sinta-accredited national journals and reputable international journals published between 2019-2024, along with relevant secondary sources. The findings reveal that only 35% of PAI teachers demonstrate high technological competence, while 45% show medium competence, and 20% remain in the low category. Key factors affecting technological competence include internal factors (age, teaching experience, and attitudes toward technology) and external factors (infrastructure availability, institutional support, and professional development opportunities). The study proposes a sustainable competency development model comprising four main stages: assessment, training, implementation, and evaluation. This model, supported by adult learning theory, has shown a 60% increase in technology-based PAI learning effectiveness. Recommendations include developing TPACK-based training programs, establishing teacher communities of practice, implementing mentoring systems, improving infrastructure support, and creating comprehensive evaluation systems. The study contributes to the understanding of technological integration in Islamic education and provides practical strategies for enhancing PAI teachers' digital competencies in elementary schools.